Seeking nontraditional approaches to collaborating and partnering with industry - Held, Bruce, 1958- (Online Rand research documents., 2002)
The US Army has a growing need to collaborate and partner with industry. This text describes three non-traditional approaches to that goal: forming real-estate, public-private partnerships; using Army venture capital mechanisms; and spinning of Army activities into federal government corporations.